Industry 4.0 in SMEs across the globe: Challenges and opportunities - Turner, Parker (New York Clanrye International, 2023)
Industry 4.0 refers to the fourth industrial revolution that began in 2011. It has revolutionized the ways in which companies carry out their operations, and manufacture and distribute their products. The industrial environment is drastically changing with the introduction of technologies such as artificial intelligence, cloud computing, Internet of things (IoT), machine learning, and data analytics. Modern smart technologies are used for analyzing and diagnosing problems that enable the companies to make better decisions without human intervention. Smart manufacturing incorporates computer-integrated manufacturing to increase automation and self-optimization of process improvements.
Keywords: Industry; Small business--Technological innovations; Small business--Management